Modelos de gestión de inventarios y su incidencia en la cadena de suministros de la industria agropecuaria de la Provincia de Los Ríos. año 2023. - Villalva Villanueva, Franklin Valentin (2024)
Inventory management models allow observing integral methodologies in the operational management of production processes, based on the use of indicators related to the efficiency and effectiveness of production costs that integrate the supply chain. This study analyzes Inventory Management Models and their Impact on the Supply Chain of the Agricultural Industry in the Province of Los Ríos, with the objective of evaluating how inventory management models impact the supply chain of the agricultural industry. The incorrect application of inventory management models is identified as a possible problem. Among the relevant results, the homogenization obtained by applying the ABC method in inventory management within the companies under study stands out. The methodology used was a mixed qualitative-quantitative approach, which included the validation of instruments by experts, which reported a reliability of 0.97, indicating instruments of high reliability. Subsequent weighting using the SERVQUAL method. This approach allowed a broad and deep understanding of the factors that influence inventory management and its impact on the supply chain in the specific context of the agricultural industry in the Province of Los Rios.